PENGARUH DISIPLIN KERJA, STRES KERJA, DAN LINGKUNGAN KERJA FISIK TERHADAP KINERJA KARYAWAN PADA PT.XYZ - Eva Fitriananta; Nur Cahyadi (Universitas Sarjanawiyata Tamansiswa, 2026)
The purpose of this research is to examine how PT. XYZ's physical work environment, levels of stress on the job, and employees' adherence to company policy affect productivity. A descriptive quantitative approach is the study technique used. This research used the saturated sample approach to recruit all PT. XYZ personnel as its population. Questionnaires were sent in order to gather data. Using the SPSS software, the data was analyzed by multiple linear regression, tests of reliability and validity, and testing of classical assumptions. Employee performance is positively and significantly impacted by work discipline, negatively and significantly by work stress, and positively and significantly by the physical work environment, according to the study's findings. These results show that a combination of an ideal physical work environment, better methods of managing stress on the job, and stricter adherence to work rules may boost productivity. Company management is required to take this research into account when they formulate strategies for human resource management that are both effective and sustainable.